(untitled) (Journal of Nepal Paediatric Society, 2022)
Introduction: Bronchial asthma is an inflammatory reversible obstructive airway disease. This study aims to determine the association between serum magnesium to calcium ratio with level of asthma control in children by comparing serum magnesium to calcium ratio between - children with well controlled, partly controlled and uncontrolled asthma. Methods: An analytical cross sectional study was done on 90 children diagnosed with bronchial asthma between five to 12 years age from January 2019 to June 2020. Children were selected from the outpatient and inpatient departments of paediatric medicine of a tertiary care medical college hospital. They were classified into well controlled, partly controlled and uncontrolled groups as per Global Initiative for Asthma (GINA) assessment of asthma control in children. The serum magnesium to serum calcium ratio of these children were compared between the groups classified. Results: Mean level of serum magnesium to calcium ratio in well controlled group was 0.29857 (SD 0.07633), partly controlled 0.2439 (SD 0.0532), uncontrolled 0.2545 (SD 0.04467), respectively. Serum magnesium to calcium ratio more than or equal to 0.3 was positively correlated with well controlled asthma. Comparisons of serum magnesium to calcium ratio of well controlled group with partly controlled, uncontrolled and both partly and uncontrolled were statistically significant. Conclusions: Higher serum magnesium to calcium ratio is associated with well controlled asthma. In our study, serum magnesium to calcium ratio more than 0.3 is significantly associated with well controlled asthma.